Case studies to accompany Bates' guide to physical examination and history taking - Prabhu, Fiona R.; Bickley, Lynn S. (Philadelphia, Pennsylvania : Lippincott Williams & Wilkins, 2007)
This case studies book is designed for the development of clinical reasoning, assessment, and differential diagnostic skills. Each case study presents with a chief complaint, brief history, and then physical examination findings. Multiple-choice exercises, matching exercises, and labeling exercises are included. Answers can be found at the end of the book. This edition includes additional cases on the older adult and other new topics covered in the Ninth Edition of Bates' Guide to Physical Examination and History Taking.
1. Beginning the Physical Examination: General Survey and Vital Signs -- 2. The Skin, Hair, and Nails -- 3. The Head and Neck -- 4. The Thorax and Lungs -- 5. The Cardiovascular System -- 6. The Breasts and Axillae -- 7. The Abdomen -- 8. Male Genitalia and Hernias -- 9. Female Genitalia -- 10. The Anus, Rectum, and Prostate -- 11. The Peripheral Vascular System -- 12. The Musculoskeletal System -- 13. The Nervous System: Mental Status -- 14. The Nervous System: Cranial Nerves, Motor, Sensory, and Reflexes -- 15. Infants Through Adolescents -- 16. The Pregnant Woman -- 17. The Older Adult -- References -- Answers and Explanations.
Includes bibliographical references.
Keywords: PHYSICAL DIAGNOSIS